Evaluasi Kebijakan Pemerintah Terhadap Pengembangan Usaha Mikro, Kecil, dan Menengah (UMKM) di Kabupaten Badung - I Nyoman Mahardhika; Ni Putu Tirka Widanti; Ida Ayu Putu Sri Widnyani; Ida Ayu Sayang Bidul (eCo-Buss, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are essential in supporting national and regional economic growth, especially as a driving force for the local economy that contributes significantly to the Gross Regional Domestic Product (GRDP) in Badung Regency, Bali. However, the development of MSMEs still faces various obstacles, such as limited access to capital, low-quality human resources, and inadequate infrastructure. This study aims to evaluate MSME development policies in Badung Regency using qualitative methods and a case study approach. Data were obtained through in-depth interviews with MSME actors, government officials, and related supporting institutions, as well as field observations and documentation. The study results indicate that existing government policies have not effectively overcome MSMEs' challenges, especially regarding access to capital and marketing. The recommendations include the need for policy innovation, increasing access to technology, developing human resource skills, and strengthening supporting infrastructure to encourage the competitiveness of MSMEs in Badung Regency